Fabrication and modeling of ultra-hard and high-strength B4C-based laminated ceramics by brazing joining. Issue 19 (1st October 2022) - Liu, Geng; Wang, Aiyang; Tang, Rong; Bai, Wenhui; Song, Yanwei; Ji, Wei; Wang, Weimin
Abstract: The improvement in the comprehensive performance in strength, toughness, and hardness is significant for advanced ceramics. In the study, we successfully fabricated laminated structural ceramics by joining ultra-hard diamond-B4 C–SiC ceramics (Cd BS) with high-strength TiB2 –B4 C ceramics (TBC) according to the brazing joining method. Brazing parameters had a significant effect on the morphology of the laminated ceramics. The optimized shear strength of the welded interface could reach 109.42 ± 2.21 MPa with a brazing layer thickness of 150 μm under the brazing conditions of 930 °C and 10 min. The results of finite element analysis suggested that the maximum residual stress at the ceramic welding interface was 229.1 MPa. The compressive stresses were distributed on the ultra-hard Cd BS ceramics side, thus enhancing the impact-resistant performance of the lightweight materials.